Resistome characterization of extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli isolated from wastewater treatment utilities in Oregon. (21st March 2022) - Easler, Maeghan; Cheney, Clinton; Johnson, Jared D.; Zadeh, Marjan Khorshidi; Nguyen, Jacquelynn N.; Yiu, Sue Yee; Waite-Cusic, Joy; Radniecki, Tyler S.; Navab-Daneshmand, Tala
Abstract: Infections resistant to broad spectrum antibiotics due to the emergence of extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae is of global concern. This study characterizes the resistome (i.e., entire ecology of resistance determinants) of 11 ESBL-producing Escherichia coli isolates collected from eight wastewater treatment utilities across Oregon. Whole genome sequencing was performed to identify the most abundant antibiotic resistance genes including ESBL-associated genes, virulence factors, as well as their sequence types. Moreover, the phenotypes of antibiotic resistance were characterized. ESBL-associated genes (i.e., bla CMY, bla CTX, bla SHV, bla TEM ) were found in all but one of the isolates with five isolates carrying two of these genes (four with bla CTX and bla TEM ; one with bla CMY and bla TEM ). The ampC gene and virulence factors were present in all the E. coli isolates. Across all the isolates, 31 different antibiotic resistance genes were identified. Additionally, all E. coli isolates harbored phenotypic resistance to beta-lactams (penicillins and cephalosporins), while 8 of the 11 isolates carried multidrug resistance phenotypes (resistance to three or more classes of antibiotics). Findings highlight the risks associated with the presence of ESBL-producing E. coli isolates in wastewater systems that have the potential to enter the environment and may pose direct or indirect risks to human health. HIGHLIGHTS: All isolates were resistant to ampicillin and first- to third-generation cephalosporins. 73% of isolates displayed multidrug resistance phenotypes. Correlation between bla CTX and resistance to fourth-generation cephalosporins. Conserved gene regions across various sequence types indicate horizontal transfer. Forty-six distinct virulence factors indicate potential for pathogenicity. Graphical Abstract